EFFECT OF DIFFERENT NPK LEVELS ON QUALITY PARAMETERS ARAMETERS OF BROCCOLI ( OF BROCCOLI (Brassica oleracea Brassica oleracea L) UNDER SOUTH GUJ L) UNDER SOUTH GUJARAT CONDITION - SONAL TRIPATHI,; NARENDRA SINGH,; V. R. NAIK,; JAIMIN NAIK,; H. M. PATEL, (The Bioscan, 2019)
A three years field experiment was conducted to study the effect of NPK levels on quality parameters of Broccoli under South Gujarat condition. There were different nineteen treatments including controls. Out of them, eighteen treatments comprising of three nitrogen levels [ 80 kg N ha -1 (N1), 120 kg N ha -1 (N2) and 160 kg N ha 1 (N3)] combined with three phosphorus levels [40 kg P2O5 ha -1 (P1), 60 kg P2O5 ha -1 (P2) and 80 kg P2O5 ha 1 (P3)] along with two levels of potassium [control (K1) and 60 kg K2O (K2)]. The results revealed that the crude protein (2.18%), TSS (0.97ºBrix) and crude fibre (2.13%) were recorded significantly higher in treatment N1 whereas level N2 resulted significantly the highest Vitamin C content (79.17 mg kg-1) in broccoli. While among P level, crude protein (2.18%) and crude fibre (2.08 %) were recorded significantly higher in treatment P1 whereas level P2 resulted significantly higher Vitamin C content (73.72 mg kg -1 ) and TSS (1.01ºBrix). Treatment combination, N2P3K2, N1P2K2 , N2P3K1 and N1P2K2 recorded significantly higher value of crude protein content (2.37%), TSS content (1.22 ºBrix), vitamin “C” content (83.13 mg 100g -1 ) and crude fiber content (2.97 %) respectively.